Evolution Of Paramedicine In Emergency Medical Services: A Systematic Review Of Role Expansion, Clinical Competencies, And Care Outcomes (The Review of Diabetic Studies, 2025)
Purpose: To systematically synthesize evidence on the historical and contemporary evolution of paramedicine within emergency medical services (EMS), focusing on role expansion, clinical competency development, and patient care outcomes.Methods: A systematic review of peer-reviewed literature published between 2010–2025 was conducted across major medical databases. Studies examining paramedic scope of practice, education, advanced clinical roles, decision-making authority, and patient outcomes in prehospital emergency care were included.Results: Findings indicate a substantial transition from transport-focused responders to autonomous prehospital clinicians. Expanded competencies in advanced airway management, cardiac care, trauma intervention, pharmacology, and community-based services were consistently associated with improved response times, clinical quality indicators, survival rates, and system efficiency.Conclusion: Paramedicine has evolved into a critical clinical discipline within emergency healthcare systems. Continued investment in education, protocol modernization, and interdisciplinary integration is essential to sustain high-quality prehospital care.